THE IMPORTANCE OF THE IMPLEMENTATION OF DRAMA ANDCULTUREIN SPEAKING CLASS (AN ETHNOGRAPHY STUDY AT STIBA IEC, JAKARTA) - Budiarto (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The traditional routines in speaking class are often based on learning materials from a handbook. It is practical because a teacher does not need to think about the syllabus, as it is described clearly in front pages in the book. In addition, by referring to the syllabus in the book, the teacher can easily prepare a lessonplan. When it comes to the implementation of teaching speaking skill, the teacher can just train students based on the topics given with certain grammar points and vocabulary coverage. However, it does not normally give more opportunity for the students to use theauthentic language and culture. Too much guiding students with certain patterns and vocabulary seems to be artificial although vocabulary and grammar are not taught explicitly in a speaking class. Furthermore, without freedom in choosing a topic, students’ ideas are too restricted and they tend to memorize language patternsaccording to the topic covered in the book.Nowadays, more and more teachers realize the importance of the implementation of drama and culture in teaching English speaking skill. However, there should be further study to see how a teacher applies drama and culture while teaching speaking skill. A research conductedat STIBA IEC Jakarta investigated the importance of the implementation of drama and culture in Speaking Class of students from the second semester in 2018.It was intended to see how the phenomena of teaching English speaking skill through drama and culture was implemented. The findings indicated that drama and culture were able to help the students use English more naturally or authentically. The students were able to see whether their English was authentic and culturally acceptable by relating to their experience or knowledge they got from drama. It showed that the more topics in drama the students practiced, the more knowledge about culture they learnt, and the more authentic or natural the language they acquired. Therefore, both teacher and students think that the implementation of drama and culture in teaching speaking skill is important.